Analysis of the participation of women in football in Indonesia - Doewes, Rumi Iqbal; Nuryadin, Islahuzzaman (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
In general, football is considered a male-dominated sport but recent trends show a significant improvement in women’s participation in the sport. The aim of this study was to identify and explain the reasons for women’s participation in football in Indonesia. A cross-sectional study was conducted with 29 female athletes of the Indonesian women’s national football team using the Participation Motivation Questionnaire (PMQ) assessed by Guttman scale. The data was analyzed using a descriptive percentage approach and then grouped based on participation criteria. The results showed that more than half of the women participants in football in Indonesia were 17 years old (53%) and had a senior high school education (66%). Most of the time, women participants were encouraged by peers (87%), parents (86%), facilities and infrastructures (97%), awareness (76%), interest (79%), attachment (87%), and loyalty (90%). Participation rates were also influenced by the existence of football clubs (100%) and the training programs implemented (100%). It is concluded that women’s football participation in Indonesia is largely influenced by micro-level factors (peers and parents), macro-level factors (existence of football clubs, their facilities and infrastructures, and their training programs), and psycho-sociological factors (awareness, interest, attachment and loyalty).